PENGARUH KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Ningmabin, Peipkon Modesta; Adi, Agung Nugroho (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Employee performance is the output produced by individuals or groups from their authority and responsibility during certain periods. The said performance is affected by several factors such as job satisfaction and work motivation. The objective of this quantitative correlational research is to analyze and assess the effects of job satisfaction and work motivation on employee performance. Using simple random sampling technique, forty employees were selected as the respondents. The research instrument was assessed through validity and reliability tests. The classical assumption test consists of normality, multicollinearity, and heteroscedasticity tests. The data analysis was conducted using multiple linear regression, F test, and t test in SPSS 25. His study finds that job satisfaction and work motivation simultaneously influence employee performance, job satisfaction affects employee performance, and work motivation has no significant effect on employee performance.